2002
DOI: 10.1590/s1517-83822002000400002
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of the antimicrobial resistence in bacteria of importance to humn infections

Abstract: In view of the intimate relationship of humans with coastal lagoons (used for recreation, tourism, water supply, etc.), the discharge of domestic effluents may lead to the establishment of routes of dissemination of pathogenic microorganisms, including microorganisms carrying genes for resistance to antimicrobials, through the surrounding human communities. The objective of the present investigation was to relate the presence of antimicrobial-resistant bacteria to the environmental characteristics of three coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
0
27
0
4
Order By: Relevance
“…Several environmental and nosocomial bacteria can contain transferable plasmids that carry genes expressing several traits, one of which is multidrugresistance to antimicrobial drugs (23)(24)(25). In fact, we found plasmids with molecular weights varying between 147 kb or more and 7 kb or less in multidrug-resistant strains isolated from especimens of patients hospitalized in different units and in different decades.…”
Section: Discussionmentioning
confidence: 77%
“…Several environmental and nosocomial bacteria can contain transferable plasmids that carry genes expressing several traits, one of which is multidrugresistance to antimicrobial drugs (23)(24)(25). In fact, we found plasmids with molecular weights varying between 147 kb or more and 7 kb or less in multidrug-resistant strains isolated from especimens of patients hospitalized in different units and in different decades.…”
Section: Discussionmentioning
confidence: 77%
“…Morosini et al (2006) reported crossresistance of ESBL-resistant enterobacteria to aminoglycosides. The aminoglycoside resistance in this study calls for serious concern, because there is a high correlation between gentamicin resistance and multiresistance profiles in nosocomial strains including ESBL-resistant enterobacteria (Meirelles-Pereira et al, 2002;Carvalho et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…According to Boehm et al (2002), the transportation of fecal bacteria in the sewage to the surf zone depends on the following conditions: oceanographic (stratification of the water column), wave, tidal range and currents. Thus, this contamination in marine waters might contribute to the establishment of resistance routes for environmental bacteria (Meirelles-Pereira et al 2002).…”
Section: Discussionmentioning
confidence: 99%